Pelaksanaan Kegiatan Pengabdian Masyarakat di Rumah Quran Aisyah Radhiallahu anha Desa Bangun Sari, Tanjung Morawa Ramadhan 1442 H, 2021 M. - Fakhrurrozi Fakhrurrozi (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2021)
Community service activities held at Rumah Quran Aisyah Radhiallahu anha call and invite the souls of daa'iyah who should be present in every Muslimah. The student of KKL STAI As-Sunnah named this service program with “wardah” (color the Ramadan with blessings) which is adapted to the nuances of the holy month Ramadan. This year, Rumah Quran held a program with the theme of